Effect of Mindfulness Sport Performance Enhancement (MSPE) to Reduce competitive state anxiety on Karate Athletes - Widhi Harita, Adiwignya Nugraha; Suryanto, Suryanto; Ardi, Rahkman (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2022)
Competitive state anxiety influences cognitive, emotional, and athlete behaviour while they have to perform perfectly in a competition. This study was conducted to analyze the effect of Mindfulness Sports Performance Enhancement (MSPE) training on competitive state anxiety of karate athletes in Surabaya. The research method used is quantitative with an experimental design. The sample in this study was 28 Karate athletes from Dojo Shiroite and INKAI in Surabaya. Those samples were selected using quota sampling. The intervention provided was an MSPE intervention adapted from Mindfulness Sports Performance Enhancement (MSPE). The data collection method was carried out using a competitive state anxiety scale adapted from The Revised Competitive State Anxiety Inventory – 2 with 17 items. The data were analyzed by paired t-test with SPSS 26. The result showed a significant decrease in the average competitive state anxiety by 9.25 points. This condition is supported by the decrease in cognitive anxiety and somatic anxiety dimension by 7.76 and 3.86 points. The decrease was also followed by an increase in the self-confidence dimension by 8.21 points. The findings in this study show the importance of continuous mental mindfulness training to improve athlete performance by overcoming competitive state anxiety. This research can also be a reference for practitioners and researchers. MSPE training can be developed as an effort to improve or solve problems related to an athlete's condition.